1971
DOI: 10.2134/agronj1971.00021962006300030002x
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Increases in a Non‐nodulating Soybean Genotype Grown with Nodulating Genotypes1

Abstract: Seeds of non‐nodulating soybean (Glycine max (L.) Merrill) genotype A62‐8 were mixed in a 1:1 ratio with seeds of nodulating genotypes ‘Delmar’ and ‘Scott’. Prior to planting, the mixtures were inoculated with 7 different strains or combinations of strains of Rhizobium japonicum. A62‐8 mixed with Delmar yielded significantly more with certain inoculum treatments than when the mixture was uninoculated. However, when mixed with Scott the yields of A62‐8 did not differ with inoculum treatments. The seed protein o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
1

Year Published

1988
1988
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 4 publications
1
12
0
1
Order By: Relevance
“…The highest seed yield was obtained with strain USDA 110. It has been previously reported that this strain has high capacity of N2-fixation which results in increasing the seed yield of soybean (Abel and Erdman, 1964;Sloger, 1969;Vest, 1971).…”
Section: Resultsmentioning
confidence: 93%
“…The highest seed yield was obtained with strain USDA 110. It has been previously reported that this strain has high capacity of N2-fixation which results in increasing the seed yield of soybean (Abel and Erdman, 1964;Sloger, 1969;Vest, 1971).…”
Section: Resultsmentioning
confidence: 93%
“…The most probable explanation is the N sparing effect (Vallis et al, 1967 andVest, 1971), since the % ~SN was not lower in nonnodulating soybean of the mixture than in the nonnodulating soybean monocrop.…”
Section: Discussionmentioning
confidence: 97%
“…A large uptake of soil N by maize, including lSN fertilizer, could have maintained a high proportion of 15N in maize such that a low rate of N transfer from nodulating soybean would not have significantly changed the percent of 1SN in the maize. For the nitrogen advantage to have occurred in the dwarf maize intercrop with nodulating soybean, some soil and fertilizer N must have been spared, by nodulating soybean, for maize (Vallis et al, 1967;Vest, 1971).…”
Section: Discussionmentioning
confidence: 99%
“…The beneficial effect of the legume on the companion grass observed in conditions of low soil mineral N status is interpreted as the result of a transfer of symbiotically fixed nitrogen from the legume to the grass (Eaglesham et al, 1981;Vest, 1971). Nitrogen transfer may occur via a number of pathways such as decay of excreta of grazing animals, decay of legume litter and nodulated roots, leaching of soluble N from living leaves and ex-cretion of amino-acids from active nodulated roots (Simpson, 1965;Vallis, 1978;Whitehead, 1970).…”
Section: Introductionmentioning
confidence: 99%
“…Although the importance of root excretion remains controversial, possibly because of difficulties to produce experimentally and so to determine quantitatively (Vallis, 1978;Whitehead, 1970), it is still evoked as a possible determinant pathway of N transference (Eaglesham et al, 1986;Haystead and Marriott, 1979;Lescure et al, 1986;Ruschel et al, 1979;Simpson, 1965;Ta and Faris, 1987;Vest, 1971;de Wit, 1966). Since the pioneering studies, which showed excretion of soluble amino-acids from legume root systems (e.g.…”
Section: Introductionmentioning
confidence: 99%